Verletzungen im Handballsport: Eine vergleichende retrospektive Untersuchung zwischen Regional- und Oberligamannschaften - Seil, R.; Rupp, S.; Tempelhof, S.; Kohn, D. (Sportverletzung Sportschaden, 1997)
To evaluate the injuries in Team Handball 186 male players out of 16 teams were questioned retrospectively at the end of a season. An important difference between practice and competition injuries could be found with an injury rate of 0.8 injuries per 1000 training hours and 13.5 injuries per 1000 playing hours. Injuries were predominant at the lower extremities with ankle injuries being the most frequent injury type. 2/3 of the playing injuries occurred in offense. 1/3 of these offense injuries could be attributed to a counter-attack. These injuries were generally more severe which lead us to a proposition of changing the rules of the game in foul plays in this situation. Elbow injuries in goalkeepers and shoulder injuries in throwers were specific for these types of players. Prophylactic braces were used by nearly 2/3 of the players.